Clinical Application of Hyperdry Amniotic Membrane in Cleft Palate Repair. (June 2023) - Fujiwara, Kumiko; Tsuno, Hiroaki; Okabe, Motonori; Yoshida, Toshiko; Imaue, Shuichi; Tomihara, Kei; Arai, Naoya; Noguchi, Makoto
Objective: To examine the safety and efficacy of hyperdry amniotic membrane (HDAM) for wound closure after palatoplasty in cleft palate patients. Methods: HDAMs were prepared by washing and drying under infrared rays and microwaves at temperatures less than 60°C using a hyperdrying device. A total of 16 cleft palate patients (8 males, 8 females), aged 1 to 3 years (mean age 1 year 9 months), received one-stage pushback palatoplasty. The remaining raw wound after surgery was covered by an HDAM and a plastic cover plate. The cover plate was removed 1 week after surgery and parameters including temperature, feeding, allergic reactions, postoperative bleeding, re-epithelialization, wound dehiscence, and infection were monitored during the follow-up period of 31.2 months. Results: All patients could adequately ingest at 5 days postoperation and after removal of the cover plate. None of the patients had a persistent fever or allergic reactions. Ingestion was feasible immediately in all patients, and no postoperative bleeding was observed during ingestion. No secondary hemorrhages were observed during follow-up. No postoperative wound dehiscence on the midline of the palate was observed. No infections were observed after the removal of the cover plate. No patients suffered from severe scar formation or contracture of the wound in the follow-up period. Hemorrhage, undue epithelialization, and scar contracture did not occur in any patient. The mean evaluation score was 7.75 points. Conclusion: HDAM can be used safely and effectively for wound closure following palatoplasty in cleft palate infants. Future studies testing the safety of patient's own amnion for palatoplasty, are required.